2022
DOI: 10.1155/2022/1980622
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Potential of the Aqueous Extract of the Mixture of Bidens pilosa (Asteraceae) and Cymbopogon citratus (Poaceae) Aerial Parts on Hypertension Induced by a Chronic Salt and Alcohol Consumption on the Rats

Abstract: High blood pressure (HBP) is currently one of the main risk factors for cardiovascular and kidney diseases. Nowadays, populations make extensive use of alternative medicine for their health problems. Bidens pilosa (B. pilosa) and Cymbopogon citratus (C. citratus) are used individually in the traditional treatment of cardiovascular disorders. This study assessed the effects of the mixture of these two plants aqueous extract on HBP in rats. Male rats (42) were divided into 7 groups of 6 rats each. Normotensive r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 40 publications
(45 reference statements)
1
5
0
Order By: Relevance
“…It is true that Hanisa et al [31] found no signifcant changes in serum markers of lipid profle in the subchronic toxicity of C. citratus. Nonetheless, the observations in the present study are in agreement with our previous study showing that the extract of the mixture improves the lipid profle of hypertensive rats [17]. Transaminases (ALT and AST) are good markers of liver integrity and function [32].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It is true that Hanisa et al [31] found no signifcant changes in serum markers of lipid profle in the subchronic toxicity of C. citratus. Nonetheless, the observations in the present study are in agreement with our previous study showing that the extract of the mixture improves the lipid profle of hypertensive rats [17]. Transaminases (ALT and AST) are good markers of liver integrity and function [32].…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have confrmed the traditional uses of these plants [7][8][9][10][11] and assessed the toxicity of each plant [6,[12][13][14]. Several scientifc studies have already been carried out on plant mixtures [15][16][17][18]. Tese two plants in mixture are also used to treat cardiovascular disorders (hypertension) in the central region of Cameroon but no data on the toxicity of the mixture are available.…”
Section: Introductionmentioning
confidence: 99%
“…This mixture caused a significant decrease in systolic, diastolic and mean blood pressure, together with a significant decrease in heart rate. Finally, in ethanol and salt-induced hypertensive Wistar rats, the oral administration of 200 mg/kg water extract of lemongrass or of a mixture of lemongrass and hairy beggarticks ( Bidens pilosa L.) for 7 weeks significantly decreased systolic, diastolic and mean blood pressure [ 103 ]. Even though these effects cannot be solely attributed to the bioactive compounds of lemongrass per se, they suggest that these herbal combinations show efficacy to decrease blood pressure, paving the way for the development of new combinations to be explored in the future [ 31 ].…”
Section: Cardiovascular Activity Of Lemongrass and Citralmentioning
confidence: 99%
“…Several studies have shown that lemongrass products exhibit a diuretic effect, which may also contribute to a decrease in blood pressure [ 29 , 103 ]. In one study, a single dose of a water extract of lemongrass was administered orally to Wistar rats and a weak diuretic activity was observed, even though no cardiovascular variables were measured and only a urinary index was calculated [ 29 ].…”
Section: Cardiovascular Activity Of Lemongrass and Citralmentioning
confidence: 99%
See 1 more Smart Citation